Work Family Conflict, Work Environment, and Workload: Impact on Employee Work Stress: Dampak Konflik Kerja-Keluarga, Lingkungan Kerja, dan Beban Kerja terhadap Stres Kerja Karyawan: Analisis Kuantitatif - Alwi Hasim; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aimed to examine the relationships between work family conflict, work environment, workload, and employee work stress in a specific organization. The research utilized a quantitative approach with hypothesis testing, involving a sample of 70 employees from a manufacturing company. Multiple linear regression analysis, coefficient determinants (R2), multiple correlation coefficient (R), f test, t test, and classical assumption tests were employed as analytical tools using SPSS version 18. Primary data were collected through questionnaires using a Likert scale, which underwent validity and reliability tests. The findings demonstrated significant effects of work family conflict, work environment, and workload on employee work stress. These outcomes contribute to our understanding of the factors influencing employee well-being in the workplace. The implications of this research may inform organizational interventions aimed at reducing work stress and improving overall employee performance and satisfaction. Highlights: The study examines the impact of work family conflict, work environment, and workload on employee work stress. Multiple linear regression analysis and statistical tests were employed for hypothesis testing. The findings demonstrate significant relationships between these factors and employee work stress. Keywords: Work Family Conflict, Work Environment, Workload, Employee Work Stress, Quantitative Analysis